CHANGE LIFE: FROM URBAN REVOLUTION TO SPACE REVOLUTION - HENRI LEFEBVRE PROJECT - Soares Pereira, Claudio Smalley [UNESP] (Univ Federal Fluminense, 2018)
The Henri Lefebvre's theory of the production of space is nowadays one of the main debated contributions in contemporary social theory when the subject is the spatiality of social life. This paper has place in this discussion. However, it draws attention to other aspects of lefebvrian theory that were little discussed and deserve a greater attention for its interlocutors part. The main argument is that Lefebvre elaborates a theoretical and practical project with the finality and revolution of space, in which would have a wider and deeper range than urban revolution, without excluded it. To change life would be necessary to revolutionize the space through the production of a new space. The intention is, therefore, to contribute for the debate about the theory of the production of space and about theoretical contributions offered by this theory to comprehend the current world.
Keywords: Change life; Space production; Project; Space revolution; Urban revolution